Davitti, E., Korybski, T., and Braun, S. (Eds.). (2025). The Routledge Handbook of Interpreting, Technology and AI (1st ed.). London: Routledge. https://doi.org/10.4324/9781003053248 (pp.448) - Dastyar, Vorya (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2025)
/